Marketing signals influencing consumer trust in online purchase context: an empirical paper - Isamudin, Nur Farihah; Ahmad Suki, Amirah (Mac Arts & Communication, 2024)
Consumer trust is crucial in online purchase decisions, particularly for luxury goods as it involves few risks such as authenticity status, information asymmetry and the nature of online shopping which is absence of feel and touch. Based on signaling theory, this study aims to analyze four factors known as marketing signals which are brand reputation, online reviews, money-back guarantee and site aesthetics on consumer trust in the context of online purchase of personal luxury goods. Using SPSS and AMOS, this study analyzed 214 data collected from consumers in Malaysia who intend to purchase or has experience purchasing personal luxury goods online through either one of various online platforms such as official brand website, third-party platforms and social media commerce. The results from the analysis showed that brand reputation and online reviews positively and significantly influence consumer trust. However, money-back guarantee and site aesthetics were found to have non-significant influence on consumer trust. Luxury marketers must ensure to build strong brand reputation in order to gain consumer trust to purchase online. In addition, luxury marketers can also consider incorporating online reviews in their own unique way to enhance consumer trust while maintaining the luxury identity online.